Топливо и материалы ядерной техники учебное пособие - Беляев Л. А. Леонид Александрович; Воробьёв А. В. Александр Владимирович; Гаврилов П. М. Петр Михайлович; Гвоздяков Д. В. Дмитрий Васильевич; Губин В. Е. Владимир Евгеньевич (Томск, Изд-во ТПУ, 2010)
Заглавие с титульного экрана